Female Early Marriage and Son Preference in Pakistan - Mughal, Mazhar; Javed, Rashid; Lorey, Thierry (The Journal of development studies, 2023)
In this study, we employ pooled data from four rounds of Pakistan Demographic and Health Survey (PDHS) to examine whether, and to what extent, does the incidence of early marriage shape the married women's perspectives on gender preference associated with reproduction. We employ a number of econometric techniques (Probit, OLS, Cox Hazard Model, IV Probit and treatment effects) and a large set of model specifications, and find significant evidence supporting the role of early marriage in perpetuating disproportionate preference for boys. Women who married before turning 18 not only state a greater desire for boys but are also less likely to stop reproduction as long as they do not have a boy. Early-age marriage is associated with 7.7-12.5 per cent higher incidence of fertility discontinuation among women without a son. This son-preferring behaviour is stronger at higher birth order and also reflects in differential spacing patterns. Women's education appears to be the strongest channel through which these effects are mediated. The divergence between early- and late-marrying women appears to have sharpened over time. The findings of this study underscore the role played by early marriage in altering the gender-specific attitudes prevalent in the society, and highlight existing gender inequality traps.